2010
DOI: 10.1248/bpb.33.198
|View full text |Cite
|
Sign up to set email alerts
|

Shuttle Vectors Derived from pN315 for Study of Essential Genes in Staphylococcus aureus

Abstract: Using the par to rep region of the 24653 bp plasmid pN315, which is present in Staphylococcus aureus strain N315, we constructed three vectors that can be shuttled between Escherichia coli and S. aureus and maintained stably in S. aureus. Due to plasmid incompatibility, the resident plasmid in S. aureus cells can be replaced via transformation with an entering plasmid, which carries a different drug resistance gene. To evaluate the applicability of this plasmid-based approach for identifying genes essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…pMNS contains the transcription terminators, Pspac promoter, lacZ , and lacI from pMutinT3 and pE194 ori , pUC ori , and the spectinomycin resistance gene from pTetON. pMNS is compatible with pKE516 [38]. Plasmids used in this study are shown in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…pMNS contains the transcription terminators, Pspac promoter, lacZ , and lacI from pMutinT3 and pE194 ori , pUC ori , and the spectinomycin resistance gene from pTetON. pMNS is compatible with pKE516 [38]. Plasmids used in this study are shown in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…To construct plasmid pNcmk, cmk (SAHV_1466) of Mu3 chromosomal DNA was amplified using the cmk-CP1 and cmk-CP2 primers (see Table S1 in the supplemental material) and was inserted into the BamHI site in the pND50 plasmid vector (12). The integrity of the cloned cmk was ascertained by sequencing the recombinant plasmid using the pND-P1 and pND-P2 primers.…”
Section: Methodsmentioning
confidence: 99%
“…From these cells, targeted integration of pMltaS at the chromosomal ltaS gene was confirmed by PCR, resulting in T772 (DltaS::pMltaS, Dspa::phleo/pM102-ltaS). Finally, T772 was transformed with pM101 (13), which is incompatible with pM102-ltaS because they possess the same replicon, but has a different marker from pM102 (namely, kanamycin resistance). A kanamycin-resistant transformant, T775 (DltaS::pMltaS, Dspa::phleo/pM101), was obtained at 30˚C.…”
Section: Protein Sera and Bacteriamentioning
confidence: 99%